Tingkat Pemanfaatan Teripang Ekonomis Penting di Perairan Kepulauan Karimunjawa - Amalo, Nancy Marcelina Reinatha; Muskananfola, Max Rudolf; Rudiyanti, Siti (Life Science, 2024)
Sea cucumbers are an economically important fishery commodity in great demand by both local and international audiences. As time goes by, the need for sea cucumbers increases and people make excessive use of sea cucumber resources until they reach the status of over-exploitation. This makes it necessary to know the level of utilization of sea cucumbers in Karimunjawa. This research was carried out on August - September 2023 in Tanjung Gelam, Karimunjawa. The purpose of this research is to find out the catch per unit effort, maximum sustainable potential/maximum sustainable yield, and the level of utilization of sea cucumbers in Karimunjawa waters. This research uses a survey method with the survey carried out to collect data regarding catches and fishing trips for fishermen directly. The data analysis method uses model calculations Schaefer. From the research results, it was found that the average CPUE production value was 4 kg/trip. The potential MSY value obtained is 2.857 kg/year with an optimum effort (f opt) of 620 trips/year. The level of utilization of sea cucumbers has an average value of 93,27% which is categorized as optimum, so there is no need to make additional efforts because the catch is already optimal and if it is added it will cause an excess catch.